Born Again, Again: Conversion in Christian Families as a Process Punctuated by Grace - Tighe, Steven (Christian education journal, 2015)
This is an examination of the experience of adolescent conversion, with particular attention to teenagers who report having made multiple commitments to Christ. Conversion of these teenagers is seen as a long process containing multiple spiritually significant commitment events. The aspects of faith that James Fowler measures to mark the transition from his mythic/literal stage to the synthetic/conventional stage are used as a framework to understand the perceived need of these teenagers to make what appear to be multiple commitments to Christ.